The Middle and Lower Cambrian salt tectonics in the central Tarim Basin, China: A case study based on strike-slip fault characterization - Qing Bian; Jibiao Zhang; Cheng Huang (Energy Geoscience, 2024)
Due to the considerable depth of the salt layers and the lack of calibration by exploratory drilling, the interpretation of the Middle and Lower Cambrian salt formations in the central Tarim Basin poses a challenge. In this paper, we apply the coupling and decoupling deformation theory in salt tectonics to analyze the No.7 fault mapped in the seismic datasets by the response characteristics of the Middle and Lower Cambrian layers. By quantifying the stratigraphic framework of the Middle and Lower Cambrian strata, we define the position of the salt layer with the seismic data. Structural decoupling is observed in the Middle and Lower Cambrian sequences in the Shuntuoguole Low Uplift, while deformation coupling is observed in these two sequences in the Shaya Uplift.